Pomegranate extract prevents skeletal muscle of mice against wasting induced by acute TNF‐α injection. Issue 4 (30th November 2016) - Rodriguez, Julie; Caille, Olivier; Ferreira, Daneel; Francaux, Marc
Abstract : Pomegranate peel is a rich source of polyphenols, the major representative being the ellagitanins, which are transformed in urolithins by the gut microbiota. This study reveals that dietary supplementation with pomegranate peel extract is able to reduce the inflammatory and catabolic responses following a single injection of TNF‐α in skeletal muscle of mice. Urolithin A is possibly the active compound since incubation of myotubes with urolithin A enables to reproduce in vitro, the effects observed in vivo. Abstract : Scope: We investigated whether punicalagin‐rich pomegranate extract (PE) protects skeletal muscle of mice against inflammation induced by an acute injection of TNF‐α. Results: Mice fed with PE or standard chow during 6 wk were injected with TNF‐α (100 ng/g) or vehicle and sacrificed 6 h later. Prior supplementation with PE prevented the loss of tibialis anterior mass induced by TNF‐α. In skeletal muscle, the activation of the NF‐κB signaling and the induction of cytokines mRNA were reduced in mice having received PE. In those mice, the activity of the Akt/mTORC1 pathway and the protein synthesis were maintained after TNF‐α injection whereas markers involved in the ubiquitin proteasome pathway were less activated. As urolithin A was the only punicalagin metabolite detectable in plasma of mice supplemented with PE, we performed in vitro experiments using a murine cell line (C2C12) to provide evidence that urolithin A is likely the active compound protecting skeletal muscle against TNF‐α‐induced inflammation. Conclusion (focus on nutritional relevance): These results suggest that supplementation with a punicalagin‐rich PE may protect skeletal muscle against an acute inflammation.